Pitching Novel Ideas to the Boss: The Interactive Effects of Employees’ Idea Enactment and Influence Tactics on Creativity Assessment and Implementation - Lu, Shuye; Bartol, Kathryn M.; Venkataramani, Vijaya; Zheng, Xiaoming; Liu, Xin (Academy of Management Journal, 2019)
Employees’ creative ideas often do not receive positive assessments from managers and, therefore, lose the opportunity to be implemented. We draw on Dutton and Ashford’s (1993) issue-selling framework to test a dual-approach model predicting that employees’ use of both high levels of idea enactment behaviors (characterized by use of demos, prototypes, or other physical objects when presenting ideas) and high levels of upward influence tactics will have an interactive effect on the extent to which their creative ideas are positively assessed by their supervisors and, in turn, implemented. We found support for this interactive effect of idea enactment and influence tactics in two studies: a field study of 192 employees and 54 supervisors in a video game and animation company and an experimental study with 264 participants. In the experimental study, we also demonstrated that the benefits of using this dual approach are more likely to accrue when selling a more novel idea rather than a less novel, more mundane one. Both studies highlight the mediating role of supervisors’ creativity assessment in implementing employees’ creative ideas.